An uncommon case of inferior vena cava injury during atrial fibrillation ablation. Issue 8 (24th August 2020) - Pastoricchio, Manuela; Dell'Antonio, Andrea; Zecchin, Massimo; Bianco, Elisabetta; Zucca, Annalisa; Biloslavo, Alan; Bortul, Marina
Abstract: A 64-year-old man underwent catheter ablation (CA) of atrial fibrillation with intracardiac echocardiography (ICE) assistance. As the probe was advanced toward the right atrium, sudden abdominal pain was felt by the patient with hypotension and tachycardia requiring fluids and vasopressors for hemodynamic stabilization. The inferior vena cava (IVC) was injured by the passing probe and open repair was then performed. To our knowledge, this is the first reported case of symptomatic IVC laceration by the probe used for ICE during CA.